Optimization of battery and wind technologies: Case of power deviation penalties - Iskeceli, Bilge Dilara; Kayakutlu, Gulgun; Daim, Tugrul; Shaygan, Amir (Elsevier BV, 2020)
Abstract Incorporation of wind power with the current power grids and electricity related markets is an arduous task because of its volatile essence. As a result, there is a need for extra capacity as backup as wind power and battery are integral to one another. This research delves into the utilization of a lithium-ion battery storage system to reduce day ahead bid changes and market integration issues that exist due to sporadic disposition of wind power in Turkey. This research uses data from a 30 MW wind farm and considers added Lithium-ion batteries. Financial analyses have been carried out with lithium-ion investment, variable costs, and current market prices considered. Net present value of both systems was discovered as positive. This research advocates the use of storage systems for the developing countries such as Turkey. It demonstrates that with the drop of battery prices, storage systems have the potential to serve as more applicable options. Furthermore, the importance of energy storage regulation for storage system to enter the market is demonstrated.
Keywords: Wind turbines -- Case studies; Engineering